2022
DOI: 10.1002/cbic.202200516
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Pathways for the Enzymatic Degradation of Poly(Ethylene Terephthalate): What Characterizes an Efficient PET‐Hydrolase?

Abstract: Bioprocessing of polyester waste has emerged as a promising tool in the quest for a cyclic plastic economy. One key step is the enzymatic breakdown of the polymer, and this entails a complicated pathway with substrates, intermediates, and products of variable size and solubility. We have elucidated this pathway for poly(ethylene terephthalate) (PET) and four enzymes. Specifically, we combined different kinetic measurements and a novel stochastic model and found that the ability to hydrolyze internal bonds in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 49 publications
(110 reference statements)
5
29
0
Order By: Relevance
“…These observations clearly confirm that the duration of the lag phase varied profoundly for the different enzymes. The data concur with a recent study from our lab [42] where it was found that HiC and TfC were inferior to LCC by yielding a longer lag phase on nano PET particles. [42] Steady-state rate of the product formation Once the lag phase had occurred, the product formation for all reactions maintained a constant rate (Figure 3A-F).…”
Section: Duration Of the Lag Phasesupporting
confidence: 92%
See 2 more Smart Citations
“…These observations clearly confirm that the duration of the lag phase varied profoundly for the different enzymes. The data concur with a recent study from our lab [42] where it was found that HiC and TfC were inferior to LCC by yielding a longer lag phase on nano PET particles. [42] Steady-state rate of the product formation Once the lag phase had occurred, the product formation for all reactions maintained a constant rate (Figure 3A-F).…”
Section: Duration Of the Lag Phasesupporting
confidence: 92%
“…The samples were quantified against authentic standards of terephthalic acid (TPA), mono(hydroxyethyl terephthalate) (MHET), BHET, and a di‐aromatic compound consisting of two ethylene glycol (EG) and two TPA moieties (TETE). TPA and BHET were purchased from Sigma‐Aldrich, while MHET and TETE were synthesized in house as described previously [42] …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fluorescence of oxidized monomers was therefore found to not be adequate in explaining PETase activity, likely because monomers are not the only output of PETase activity (Pirillo et al, 2021). Indeed, PETase also produces oligo (ethylene terephthalate) (OET) (Schubert et al, 2022) defined here as any soluble PET hydrolysis product containing more than one terephthalate unit. Because OET has, by definition, multiple aromatic groups, its oxidation products will in turn have higher extinction coefficients than its monomeric counterparts, increasing fluorescent signal.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the enzymatic capacity to adsorb and turn-over during PET chain hydrolysis were recently observed to follow a tradeoff [ 143 ]. For these reasons, the biochemical kinetics and the mechanism of enzymatic PET degradation should be studied in detail to select the best enzymes and reaction conditions under which both the PHE activity is optimal and the PET polymer is most degradable, prior to scaling up the process [ 144 ]. Moreover, it is critical to set up a standard assay condition to compare different PHEs (different conditions are used for the enzymes reported in Table 4 ).…”
Section: Biotechnological Systems Applied To Plastic Depolymerization...mentioning
confidence: 99%